A Comprehensive Review on the Optical Micro-Electromechanical Sensors for the Biomedical Application - Upadhyaya, Anup M.; Hasan, Mohammad Kamrul; Abdel-Khalek, S.; Hassan, Rosilah; Srivastava, Maneesh C.; Sharan, Preeta; Islam, Shayla; Saad, Asma Mohammed Elbashir; Vo, Nguyen (Frontiers in Public Health, 2021)
This article presents an overview of current developments in optical MEMS in biomedical applications. Optical MEMS is a particular class of MEMS technology. It is a combination of micro-optics, mechanical elements, and electronics, called MOEMS, i.e., Micro Opto Electro Mechanical System. Optical MEMS comprises sensing and influencing optical signals on micron-level by incorporating mechanical, electrical, and optical systems. Optical MEMS devices are widely used in inertial navigation, accelerometers, gyroscope application, and many industrial and biomedical applications. Due to its miniaturized size, insensitivity to electromagnetic interference, inexpensive and lightweight, it can be easily integrated into the human body with a suitable design. This study presents a comprehensive review of 132 research articles published on photonic MEMS in biomedical applications, that uses the qualitative method to find the recent advancement, challenges, and issues. The paper also identifies the critical success factors applied to design the optimum photonic MEMS devices in biomedical applications. With the systematic literature review approach, the results show that the key design factors having a significant impact on design, application, and future scope of work. The literature of this paper suggests that due to the flexibility, accuracy, design factors efficiency the fiber bragg grating (FBG) sensors demand has been increasing for various photonic devices. Except for fiber bragg grating sensing devices, another sensing system such as optical ring resonator, Mach Zehnder interferometer, and photonic crystals are used, still shows experimental stages in the application of biosensing. Due to the requirement of sophisticated fabrication facilities and integrated systems, it's a tough choice to consider the other photonic system. Miniaturization of complete FBG device for biomedical application is the future scope of work, even though there is a lot of experimental work considered with an FBG sensing system, commercialization of final FBG device for a specific application has not seen noticeable progress in the past.